2006
DOI: 10.1520/jai100549
|View full text |Cite
|
Sign up to set email alerts
|

Hertzian Fracture, Kinetic Friction and the Mechanical Impact LOX Compatibility Testing of Polymers and Polymer Matrix Composites

Abstract: A cascade of probabilistic mechanisms is proposed to better understand the 72 ft-lbs mechanical impact in liquid oxygen ignition threshold sensitivity testing of polymeric and polymer matrix composite materials. This model teams the well established and understood mechanisms of Hertzian fracture and kinetic friction. In conjunction they explain the mechanical fracturing of the specimen and the very rapid transformation of the test's mechanical energy into temperature rising heat energy. The model also provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…The test equipment, parameters and steps were standardized (ASTM D2512, ASTM G86) [9,17,142]. According to ASTM test standard, the specimen of the material is placed at the bottom of an aluminum cup filled with LOX, a flat-tipped steel pin resting on the specimen, and then a 10 Kg plummet drop from 1 m height to strike the steel pin(Figure 12a) [142,[144][145][146][147]. During the test, any explosion, burning, noticeable ash, or charring of specimen is considered as a reaction.…”
Section: The Acceptance-testing Methods Of Materials Used In the Liquid Oxygen Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The test equipment, parameters and steps were standardized (ASTM D2512, ASTM G86) [9,17,142]. According to ASTM test standard, the specimen of the material is placed at the bottom of an aluminum cup filled with LOX, a flat-tipped steel pin resting on the specimen, and then a 10 Kg plummet drop from 1 m height to strike the steel pin(Figure 12a) [142,[144][145][146][147]. During the test, any explosion, burning, noticeable ash, or charring of specimen is considered as a reaction.…”
Section: The Acceptance-testing Methods Of Materials Used In the Liquid Oxygen Environmentmentioning
confidence: 99%
“…It has been concluded that it is a strict "pass/fail" test that material must meet if they are to be used in the LOX system. Based on the test standard (ASTM D2512-95), Gerzeski proposed a cascade of probabilistic mechanisms that teams Hertzian fracture and Kinetic friction to study the mechanical impact in LOX ignition threshold sensitivity testing of polymer and polymer composites [144]. A portion of the mechanical impact energy is transformed into thermal energy and a local hot spot formed in the specimen.…”
Section: The Acceptance-testing Methods Of Materials Used In the Liquid Oxygen Environmentmentioning
confidence: 99%
See 2 more Smart Citations